2018
DOI: 10.3390/ma11122523
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Preparation of Chitosan/Clay Microspheres: Effect of Process Parameters and Clay Type

Abstract: This work aimed to prepare chitosan/clay microspheres, by the precipitation method, for use in drug carrier systems. The influence of the process parameters, particularly two airflows of the drag system (2.5 and 10 L·min−1) on the microspheres physical dimensions and properties, such as microstructure, degree of swelling and porosity were evaluated. The samples were characterized by optical microscopy (OM), scanning electron microscopy (SEM) and X-ray diffraction (XRD). Water absorption and porosity tests were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…The diffraction pattern of CS, as shown in Figure 6, exhibited two major crystalline peaks at 10.8 • and 20.0 • , which confirms the partial crystallinity of the polymer, in agreement with previously reported results [55][56][57][58]. These peaks (10.8 • and 20.0 • ) are typical fingerprints of chitosan related to hydrated and anhydrous crystals, respectively [56].…”
Section: Xrd Analysissupporting
confidence: 90%
“…The diffraction pattern of CS, as shown in Figure 6, exhibited two major crystalline peaks at 10.8 • and 20.0 • , which confirms the partial crystallinity of the polymer, in agreement with previously reported results [55][56][57][58]. These peaks (10.8 • and 20.0 • ) are typical fingerprints of chitosan related to hydrated and anhydrous crystals, respectively [56].…”
Section: Xrd Analysissupporting
confidence: 90%
“…It is evident that the microsphere diameter will in uence the structure. In meanwhile, we observed that tight external structures are produced on the surface of microspheres of CS in the studies [28,29] . The microsphere diameter may have an impact on the hemostatic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers and their coworkers have performed several trials for developing efficient adsorbents from chitosan by incorporating different substrates such as sand [16], perlite [17], ceramic alumina [18], oil palm ash [19], calcium alginate [20], magnetite [21], polyurethane [22], cotton fiber [23], cellulose [24], polyvinyl alcohol [25], polyvinyl chloride [13], etc. However, the major focus has been on clay minerals [5][6][7][26][27][28][29][30][31][32][33]. Clay minerals are attractive immobilization/support materials for chitosan owing to their relatively large available surface areas [34].…”
Section: Introductionmentioning
confidence: 99%